Rosemary flowers as edible plant foods: phenolic composition and antioxidant properties in caenorhabditis elegans - Moliner, Cristina (2018)
Rosmarinus officinalis L., commonly known as rosemary, has been largely studied for its wide use as food ingredient and medicinal plant; less attention has been given to its edible flowers, being necessary to evaluate their potential as functional foods or nutraceuticals. To achieve that, the phenolic profile of the ethanolic extract of R. officinalis flowers was determined using LC-DAD-ESI/MSn and then its antioxidant and anti-ageing potential was studied through in vitro and in vivo assays using Caenorhabditis elegans. The phenolic content was 14.3 ± 0.1 mg/g extract, trans rosmarinic acid being the predominant compound in the extract, which also exhibited a strong antioxidant capacity in vitro and increased the survival rate of C. elegans exposed to lethal oxidative stress. Moreover, R. officinalis flowers extended C. elegans lifespan up to 18%. Therefore, these findings support the potential use of R. officinalis flowers as ingredients to develop products with pharmaceutical and/or nutraceutical potential.